Editorial: peristomal pyoderma gangrenosum—a challenge for patients, healthcare professionals and research. Issue 2 (26th June 2020) - Townsend, Tristan; Probert, Chris
Abstract : LINKED CONTENT This article is linked to Wang et al paper. To view this article, visit https://doi.org/10.1111/apt.15766 .